A clinical study of evaluation of tympanoplasty with mastoidectomy in mucosal chronic otitis media - Mahajan, Ritesh; Abraham, Nidhi; T. M., Nagaraj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic suppurative otitis media (CSOM) is one of the most common ear diseases in developing countries with a varying incidence of 3% to 57%. It the disease process is further divided into mucosal type and squamosal type depending on clinical presentation. The mainstay of therapy in CSOM remains surgery which aims at eradication of disease and restoring the hearing mechanism. The main objective of our study was to evaluate the changes and impact of tympanoplasty with mastoidectomy as a surgical treatment modality in mucosal type of CSOM. Methods: A prospective study was conducted in Rajarajeshwari Medical College and Hospital between November 2015 and June 2017, involving 50 patients with mucosal type of chronic otitis media. These patients, after complete clinical examination and hearing analysis, underwent tympanoplasty with cortical mastoidectomy. Follow-up of the patients was done at one month and three months after the surgery where the parameters recorded preoperatively were assessed. Results: The graft uptake three months after the surgery was 94%. Patients reported a subjective improvement in symptoms of ear discharge, decreased hearing, earache and tinnitus to 94%, 70%, 86% and 78% respectively. There was hearing improvement in ears that had discharge preoperatively and those ears that did not. Conclusions: Chronic suppurative otitis media is a very common problem and it can lead to recurrent ear discharge and hearing problems. Timely intervention is necessary as early diagnosis results in good surgical outcomes and can make an impact on patient’s quality of life.